Care of the Patient With IBD Requiring Hospitalisation During the COVID-19 Pandemic. (29th July 2020) - Allez, Matthieu; Fleshner, Phillip; Gearry, Richard; Lakatos, Peter L; Rubin, David T
Abstract: The management of IBD has been highly affected in the context of the COVID-19 pandemic, with restriction of hospitalisations and unprecedented redeployment of health care resources. Hospital admissions of IBD patients should be limited to reduce the risks of coronavirus transmission. However, delaying hospitalisation of IBD patients with severe or complicated disease may increase the risk of poor outcomes. Delaying surgery in some cases may increase the risk of disease progression, postoperative morbidity, and disease complications. IBD patients who are infected with SARS-CoV-2 may have a higher risk of poor outcomes than the general population, potentially related to concomitant medications, especially corticosteroids. There is no evidence today that IBD patients with COVID-19 have worse outcomes if they receive immunosuppressant medications including thiopurines, biologics, and novel small molecules. This article summarises recommendations by the international membership of IOIBD regarding hospitalisations of IBD patients, either for active or complicated IBD or for severe COVID-19, and for management of IBD patients according to SARS-CoV-2 infectious status.